PTH-276 Adenocarcinoma of rectum – a composite of 3 different subtypes with varying outcomes?. (22nd June 2015) - Vallam, KC; Desouza, A; Bal, M; Engineer, R; Patil, P; Saklani, A
Abstract : Introduction: Considerable confusion exists with regards to the terminology of mucin secreting adenocarcinomas of the rectum. The WHO classification system needs to be followed accurately for comparing the outcomes of mucinous and signet ring cell carcinomas. We hypothesised that clinico-pathological outcome measures like margins, tumour regression grade, recurrence rates and survival vary with histology. Method: We conducted a retrospective analysis of a prospectively maintained database. All Stage I-III rectal adenocarcinoma patients were included. Results: Between May 2010 and August 2013, 273 patients underwent curative resection. Both the mucin secreting variants were more common in young age and presented at a more advanced stage.14%of tumours had signet ring cell histology whereas 8% had mucinous histology. 54% and 48% of signet ring cell carcinoma (SRCC) and mucinous adenocarcinoma (MAC) patients were node positive in contrast to the classical variant (30%). CRM positivity was 24% with MAC and 19% with SRCC as compared to 4% with the classical variant. The DFS among the classical and mucinous variants was 38.5 and 37.4 months, respectively, whereas it was 28.6 months in the SRCC group. OS did not differ significantly. Conclusion: There is a high incidence of aggressive mucin secreting variants in India. There exists a spectrum of adenocarcinomas of rectum with progressively worsening outcomes from classical to MAC to SRCC. These aggressive variants might warrant more aggressive resections. Disclosure of interest: None Declared.